KEEFEKTIFAN PELAKSANAAN UJIAN SEMESTER GASAL DENGAN SISTIM BERGILIR KELAS XI JURUSAN OTOMOTIF SMK YAYASAN PENDIDIKAN (YP) DELANGGU - Pratamawati, Lucyana (Jurnal Nosel, 2015)
The goal of this research is to get the view of (1) the effectiveness of odd semester exam with rotating system in preparation aspect, (2) the effectiveness of odd semester exam with rotating system in performing aspect, (3) the effectiveness of odd semester exam with rotating system in student?s assessment aspect, (4) Student?s studying motivation in attending odd semester exam with rotating system, (5) Student?s studying achievement in odd semester exam with rotating system on technique vocational subject. This research was held in SMK Yayasan Pendidikan (YP) Delanggu. This research was evaluative research type by using descriptive research method. The population of this research was 113 students from 4 classes. The technique for taking sample used proportional random sampling while for determining the sample size used Nomogram Harry King. The technique for collecting variable data of the effectiveness of intermittent used questionnaire technique and interview. Whereas in student?s studying achievement variable used documentation technique. Validation test was done with correlation product moment technique for Pearson while reliability test was done with Cronbach Alpha. The results of this research show that; (1) the effectiveness of odd semester exam with rotating system in preparation aspect is classified as good; (2) the effectiveness of odd semester exam with rotating system in performing aspect is classified as good; (3) the effectiveness of odd semester exam with rotating system in student?s assessment aspect is classified as good; (4) Students? studying motivation in attending odd semester exam with rotating system is classified as good, (5) Students? studying achievement on technique vocational subject for XI grade is classified as good.